REAL APPLICATION OF IMMERSIVE TECHNOLOGIES IN BIOMEDICAL EDUCATION - Mintser, O.P.; Mokhnachov, S. I.; Hanynets, P. P.; Sarkanych, O. V.; Vember, Ye. V. (Medical Informatics and Engineering, 2025)
Background. Issues of development, application and prospects of immersive technologies in health care and biomedical education are considered. The purpose of the study was to analyze the possibility of using immersion technologies in biomedical education, analyze their advantages and limitations, as well as prospects for further development. Materials and methods. Results. Immersive technologies are already a promising tool for bio- medical practice and education today. However, current studies for medical students focus too much on questions related to surgery and anatomy. Immersion technology is widely accepted and used in both biomedical practice and education to reduce existing deficiencies. Conclusions. Interactive technology can create a student–centered learning process, allowing them to have an interactive and personalized hands–on experience using the translation capability and portability of VR/AR/MR/XR devices. According to the results of meta–analyses, the introduction of immersion technology in medical training can significantly increase the indicators of the ability of students and postgraduates to perform surgical procedures. Given these advantages, it is important to consider the possibility of widespread adoption of immersion technology in biomedical practice and education.